Online Education and Contingent Faculty: An Exploratory Analysis of Issues and Challenges for Higher Education Administrators (Perspectives on Online Education) - Justin C. Ortagus; Luke J. Stedrak (Educational Considerations, 2013)
With the growth of the popularity and accessibility of online courses, higher education administrators are under tremendous pressure to keep pace with rapidly evolving conditions related to online learning.
Keywords: online; education; exploratory; analysis; challenges; higher education; administrators; student; enrollment